Leaf morphology and chlorophyll fluorescence characteristics of mulberry seedlings under waterlogging stress - Liangyi Rao; Siyuan Li; Xue Cui (Scientific Reports, 2021)
Abstract Because of its high flooding tolerance, in recent years, mulberry has become a tree species that is used in plant restoration in impact zones in reservoir areas. Therefore, 3-year-old potted forage mulberry seedlings were used to investigate the mechanism of mulberry adaptation to flooding stress. An indoor simulated flooding method was adopted to study the morphology of mulberry seedling leaves and the changes in leaf chlorophyll fluorescence parameters and fluorescence imaging under different flooding times and depths. The results showed that the leaves of mulberry seedlings treated with shallow submergence remained healthy during the flooding period, while the leaves of mulberry seedlings treated with half submergence and full submergence showed different degrees of waterlogging symptoms in the middle and late flooding periods and formed adventitious roots at the base of the stem. Most of the chlorophyll fluorescence parameters decreased at the beginning of flooding, but the steady-state degree of closure of PS II reaction centres (1-qP_Lss) increased significantly. In the later stage of flooding, the fluorescence parameters showed relatively stable trends. Based on these results, we conclude that mulberry has high flooding tolerance due to a combination of morphological and physiological responses.